Is placebo analgesia for heat pain a sensory effect? An exploratory study on minimizing the influence of response bias - Laura K. Case; Claire M. Laubacher; Emily A. Richards; Matthew Grossman; Lauren Y. Atlas; Scott Parker; M. Catherine Bushnell (Neurobiology of Pain, 2019)
We explored the ongoing question of whether placebo analgesia alters afferent nociceptive processing in a novel paradigm designed to minimize the role of response bias in placebo measurement. First, healthy adult participants received a standard heat placebo induction and conditioning procedure using a topical “analgesic” cream applied to one arm. During a subsequent placebo testing procedure, participants rated stimuli on the placebo-treated arm and untreated arm, using a task that minimized subjects’ ability to guess the expected response, thus reducing experimenter demand. Retrospectively participants reported moderate analgesia effectiveness (mean = 5.3/10), but for individual temperature ratings, only 2 subjects exhibited a perceptual placebo response >5 points. Next, these subjects completed a novel, exploratory task designed to measure changes in inter-arm in discriminative accuracy that would be expected from changes in afferent nociception. Both placebo responders (but no non-responders) showed reduced discriminative ability when the hotter stimulus occurred on the placebo arm, an effect consistent with alterations in nociceptive afferent flow and unlikely to be caused by response bias. Keywords: Placebo, Analgesia, Sensory discrimination, Pain, Intensity